Evaluation of PARP-1 by immunohistochemistry in a sample of Iraqi patients with gastric cancer - Mwafaq, Raghad Khalid; Abbas, Amal Khudair; Abdullah, Leith Abdul Hussein (Iraqi Journal of Science, 2022)
PARP-1 is a protein enzyme with a major role in DNA repair that is overexpressed in many malignancies. It is correlated with susceptibility and metastasis to lymph nodes in gastric cancer (GC). The objective of the present investigation is to estimate PARP1 expression in patients with gastric cancer and detected if it could be used as a predictive marker. Furthermore, we aimed to find the correlation between PARP1 expression and clinicopathological parameters, such as gender, age, invasion depth, histopathological type, involvement of lymph nodes, grade, and stages of GC. This is a retrospective study from the period 2018-2020. Fifty randomly selected subjects (10 normal and 40 GC) were examined for formalin-fixed, paraffin-embedded blocks (FFPE) of stomach tissue . The diagnosis reports were collected from the Pathology Department of the Gastroenterology and Hepatology Teaching Hospital and some private hospitals in Baghdad, Iraq. Hematoxylin and eosin (H&E) and immunohistochemical (IHC) staining of PARP1 were applied for the histological sections. Statistical analysis was accomplished by SPSS system at P<0.05. There were significant differences between the patients and control groups in the expression level of PARP1. There were also significant correlations between PARP1 expression and each of the histopathological subtype, grade, invasion depth, involvement of lymph node, and stages in patients. However, non- significant associations were found between the expression and the age and gender of patients. These results indicate that PARP1 could be employed as a good prospective marker for gastric cancer.